26‐1: Invited Paper: High Efficiency and High Stability Exciplex‐Based OLEDs. Issue 1 (30th May 2018) - Sarma, Monima; Wong, Ken-Tsung; Liu, Shun-Wei; Hung, Wen-Yi
Abstract : Organic materials exhibiting thermally activated delayed fluorescence (TADF) are an outstanding class of functional materials that have witnessed a significant development in recent years. Besides the pure TADF emitters, a new class of efficient TADF‐based OLEDs have also been fabricated which encompasses the intermolecular charge transfer between physically blended electron donor and acceptor moieties. In such systems, the electron and hole are positioned on two different molecules, thereby giving small exchange energy and thus, the ΔEST values are observed to be very small in the range 0−0.05 eV, even smaller than that of pure TADF materials. Consequently, exciplex‐based OLEDs have the potential to maximize the contribution from TADF and realize theoretical 100% internal quantum efficiency. As a result, the challenging task of achieving small ΔEST in organic systems has been resolved. In this paper, we demonstrated the molecular design strategy of using " remote steric effect" on the donor molecules for improving the efficiency of exciplex‐based OLEDs and the importance of acceptor structure on the stability of exciplex‐hosted phosphorescent OLEDs.